Kekuatan Ekonomi Rakyat dan Pengaruhnya terhadap Kemajuan Indonesia - Kogoya, Rudi (Global and Policy Journal of International Relations, 2020)
ABSTRACTIn this paper, we will discuss the importance of the people's economic power, especially rural areas in order to strengthen Indonesia‘s economic power. In a global system full of conflicts of interests each country will try to put forward capabilities in a complex relationship, including the desire to fulfill economic and political needs. One of the key indicators for a country to be classified as a developed or prosperous country, can be observed from how high its per capita income or how far a country manages to solve its poverty’s problem. This welfare’ measurement should not only be observed only in urban areas, but should also reach much wider areas, including the rural sectors. Ideally, it is not only observed by looking at urban areas, but should also cover all areas including the rural area. As an archipelago state, inequality in development has been the main problem in Indonesia, since it can be found that there are several regions which are more advanced in terms of development compared to the others. The government's willingness to introduce people’s economy in less developed areas is needed, by increasing economic cooperation with foreign investment or international markets. Besides, the government had to encourage regional stakeholders to increase their qualifications and capabilities. Since there are a lot of imported goods circulated in local market share, such as imported garlic, to prevent a food crisis in the midst of COVID-19 outbreak. Whether this condition is classified as a sign of deterioration in economic productivity and how far it affects people's economy, it will be discussed comprehensively in this paper.Key Words: People’s economic power, State Economic Power, Regions.Dalam tulisan ini, kita akan membahas pentingnya kekuatan ekonomi rakyat, terutama di daerah, dalam rangka memajukan ekonomi nasional. Dalam sistem global yang begitu penuh dengan konflik kepentingan, suatu negara akan berusaha menunjukkan kemampuan masing-masing dalam suatu hubungan. menantang, kepentingan-kepentingan ini tidak dapat dipisahkan dari keinginan untuk memenuhi kebutuhan ekonomi dan politik. Salah satu faktor bagi suatu negara untuk maju atau makmur adalah ketika pendapatan masyarakat tinggi atau bebas dari kemiskinan. Kesejahteraan ini tidak hanya diukur dengan melihat daerah perkotaan, tetapi juga harus mencakup semua wilayah yang dimaksud oleh desa. Hanya saja pembangunan di wilayah Indonesia masih mengalami ketimpangan, ada daerah yang lebih maju sementara daerah lain masih jauh tertinggal. Di sini kita membutuhkan upaya maksimal dari pemerintah untuk membantu memperkenalkan ekonomi rakyat di kawasan itu ke negara-negara asing dan pasar internasional. Dan juga perlu mendorong semua sektor ekonomi di daerah agar lebih berkualitas. Karena apa yang ditemukan banyak barang atau produk dari luar negeri yang masuk (impor) ke Indonesia, misalnya impor bawang merah putih dengan alasan mencegah krisis pangan di tengah wabah korona ini merupakan pertanda bahwa produktivitas dan ekonomi rakyat melemah. Dalam makalah ini kita akan membahas semua hal itu.Kata-Kata Kunci: Kekuatan ekonomi masyarakat, Kekuatan Ekonomi Negara, Daerah.